Contributions to the taxonomy of the mugilid genus Chelon Artedi (Teleostei: Mugilidae), with a major review of the status of C. persicus Senou, Randall & Okiyama, 1995 - Thieme, Philipp; Bogorodsky, Sergey V.; Alpermann, Tilman J.; Whitfield, Alan K.; Freitas, Rui; Durand, Jean-Dominique (Zootaxa, 2022)
New data based on multigene phylogenetic analyses using the COI, 16S, and cytb genes and subsequent molecular species delimitation revealed that the mugilid genus Chelon contains 11 species. Of these, two species, Chelon sp. A and Chelon sp. B, remained unidentified in previous studies. While Chelon sp. B seemingly is a close relative to C. dumerili (Steindachner, 1870), no more detailed information were provided for Chelon sp. A which is present along the east coast of South Africa. Genetic analyses performed in this study, revealed that specimens from the Arabian/Persian Gulf and the Red Sea are nested within one genetic lineage alongside Chelon sp. A. Morphological, morphometric, and meristic analyses of specimens from all three areas demonstrated that they belong to Chelon persicus Senou, Randall & Okyiama, 1995. Chelon persicus was originally described in the genus Chelon but was later placed either in the genus Liza or Planiliza. However, results presented herein confirm its placement in Chelon and its distribution range is extended in the Western Indian Ocean from the type locality (Arabian/Persian Gulf) west to the Red Sea and south to South Africa. Further, the uncertain validity of the recently described Chelon caeruleus Deef, 2018 from the Mediterranean Sea and a previously proposed generic character distinguishing Chelon from Planiliza and Parachelon, the shape of the paired postzygapophyses of the second vertebra, are briefly discussed.